Pengembangan Modul Ajar Digital Berbasis Flipbook untuk Meningkatkan Pemahaman Konsep IPAS Pada Siswa Kelas IV SD - Alfikhairina Alfikhairina; Sarah Fazilla; Lisa Lisa (Indonesian Journal of Elementary Education and Teaching Innovation, 2025)
In the current era of revolution, the world of education is required to follow technological developments and utilize them to facilitate the learning process. However, currently in designing learning, many teachers still only use teaching modules in the form of printouts on paper so that learning activities are very monotonous and less interesting.The purpose of this research is to produce a digital teaching module product in the form of flipbook which focuses on learning science materials on the state of matter and its changes which can help the success of the learning process through more interesting and easy-to-understand learning. The type of research conducted is development research (Research and Development) using the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation and evaluation. The data collection methods used were questionnaires, sheets pretest and posttest, and observation sheets. The results of this study indicate that the digital teaching module that has been developed is very valid with a validation percentage of 96% and 88% by the validator, very practical with a percentage of 96%, very effective with a percentage of 92% for the student response questionnaire, 99% for the teacher activity observation sheet and 96% for the student activity observation sheet, and can improve students' understanding of concepts in learning with an N-Gain value between 0.4-1 which indicates medium and high criteria results. This is shown by the positive response and increased understanding of students' concepts related to the science material being studied.